2005
DOI: 10.4049/jimmunol.174.7.4081
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Post-Thymic Development of Regulatory CD4+25+ T Cells Contributes to Diabetes Pathogenesis in BB Rats

Abstract: One of the BB rat diabetes (diabetes mellitus (DM)) susceptibility genes is an Ian5 mutation resulting in premature apoptosis of naive T cells. Impaired differentiation of regulatory T cells has been suggested as one possible mechanism through which this mutation contributes to antipancreatic autoimmunity. Using Ian5 congenic inbred rats (wild-type (non-lyp BB) and mutated (BB)), we assessed the development of BB regulatory CD8−4+25+T cells and their role in the pathogenesis of DM. BB rats have normal numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 51 publications
5
57
0
1
Order By: Relevance
“…The results of this analysis have been previously reported (4). Nonlymphopenic, ACI.1u, and BB Non-Lyp inbred strains that are homozygous for wild type Gimap5 have been previously described (28,29).…”
Section: Animalsmentioning
confidence: 74%
See 3 more Smart Citations
“…The results of this analysis have been previously reported (4). Nonlymphopenic, ACI.1u, and BB Non-Lyp inbred strains that are homozygous for wild type Gimap5 have been previously described (28,29).…”
Section: Animalsmentioning
confidence: 74%
“…Therefore, this T cell subset was evaluated in Ptpn22 congenic 2BAa and 2BAb rat donors. It has previously been demonstrated that the Gimap5 null mutation of the BBDP strain severely compromises the function and survival of CD4 + 25 + Foxp3 + Tregs once they exit the thymus (29). To circumvent this problem, we generated induced Tregs (iTregs) from ex vivo naive CD4 + 25 2 T cells congenic for rat Ptpn22 as previously described (14,30).…”
Section: The Bbdp Ptpn22 Allele Influences Treg Abundance and The Devmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons why the gut of the BBdp rat is a site of wheat protein-induced CD4 + T cell proliferation are not known, but could be related to the low frequency of CD4 + CD25 + T regulatory cells and the increased frequency of antigen-presenting cells (Fig. 5) [46]. The development of enteropathy in the BBdp gut by as early as 30 days [10] could set the stage for the continuing inflammatory damage and increased permeability [11,47] that has been linked to diabetes outcome [48] and is reported to be diet-modifiable [14,47].…”
Section: Discussionmentioning
confidence: 99%